Developing as Teachers and as Researchers: Emerging Professionals’ Experiences with Cooperative Inquiry - Laura Bower-Phipps; Maria Cruz; Cristina Albaladejo; Arlette Johnson; Thomas Homa (Networks: An Online Journal for Teacher Research, 2016)
This article details the second cycle of cooperative inquiry undertaken by emerging educators who self-identify as “other” because of gender, language, ethnicity, and/or sexual orientation. The current cycle focuses on the impact participation in cooperative inquiry had on researchers’ teaching practices. Data sources include transcripts of group discussions and reflective writing completed six months, eighteen months, and two years after the completion of the first cycle of cooperative inquiry. Findings suggest that as a result of engagement in cooperative inquiry, the teacher/researchers established practices to decrease isolation, build unity, and understand students’ backgrounds. Teacher/researchers viewed themselves as advocates for diversity within the classroom, took a collaborative approach to teaching, and came to see research as an essential element of effective teaching.